Influence of cognitive impairment on the institutionalisation rate 3 years after a stroke. Issue 1 (4th September 2006) - Pasquini, M; Leys, D; Rousseaux, M; Pasquier, F; Hénon, H
Abstract : Background and purpose: Pre-existing cognitive decline and new-onset dementia are common in patients with stroke, but their influence on institutionalisation rates is unknown. Objective: To evaluate the influence of cognitive impairment on the institutionalisation rate 3 years after a stroke. Design: (1) The previous cognitive state of 192 consecutive patients with stroke living at home before the stroke (with the Informant Questionnaire on COgnitive Decline in the Elderly (IQCODE)), (2) new-onset dementia occurring within 3 years and (3) institutionalisation rates within 3 years in the 165 patients who were discharged alive after the acute stage were prospectively evaluated. Results: Independent predictors of institutionalisation over a 3-year period that were available at admission were age (adjusted odds ratio (adjOR) for 1-year increase  = 1.08; 95% confidence interval (CI) 1.03 to 1.15), severity of the neurological deficit (adjOR for 1-point increase in Orgogozo score = 0.97; 95% CI 0.96 to 0.99) and severity of cognitive impairment (adjOR for 1-point increase in IQCODE score = 1.03; 95% CI 1 to 1.06). Factors associated with institutionalisation at 3 years that were present at admission or occurred during the follow-up were age (adjOR for 1-year increase = 1.17; 95% CI 1.07 to 1.27) and any (pre-existing or new) dementia (adjOR = 5.85; 95% CI 1.59 to 21.59), but not the severity of the deficit of the neurological deficit. Conclusion: Age and cognitive impairment are more important predictors of institutionalisation 3 years after a stroke than the severity of the physical disability.